2013
DOI: 10.1002/j.1532-2149.2013.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses and morphological changes of radiofrequency‐induced rat sciatic nerve fibres

Abstract: PRF-induced pain relief may be due to temporary blockage of nerve signals through the nerve pathway responsible for reversible neuronal depression. However, CRF-induced pain relief may be due to permanent blockage of nerve signals through other nerve pathways. Therefore, CRF could be applied to chronic inflammatory models used to study the mechanism of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Pulsed radiofrequency is a short intermittent pulse with 480 ms heat dissipation interval so that the temperature acting on the tissue does not exceed 42 • C. It does not cause nerve damage (Choi et al, 2014), only plays a role in neuromodulation (Lee et al, 2015). Therefore, PRF can act on the cervical nerve root for upper extremity PHN.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed radiofrequency is a short intermittent pulse with 480 ms heat dissipation interval so that the temperature acting on the tissue does not exceed 42 • C. It does not cause nerve damage (Choi et al, 2014), only plays a role in neuromodulation (Lee et al, 2015). Therefore, PRF can act on the cervical nerve root for upper extremity PHN.…”
Section: Introductionmentioning
confidence: 99%
“…was found to be exclusively expressed in astrocytes (50). Meanwhile, PRF may activate the expression of several types of cytokines (40). Overall, PRF application can directly and indirectly modulate neuron-glia-mediated spinal sensitization and neuroinflammation.…”
Section: Delayed Prf Effects: Prolonged Analgesia and P-erk Inhibitiomentioning
confidence: 99%
“…Though PRF can exert both thermal field (T-field) and electric field (E-field) effects, it generates stronger Efield and transmembrane potentials in neurons, but much lower T-field and temperature in comparison with CRF (8). E-field of PRF causes various degrees of microinjury in DRG neurons (10,(12)(13)(14)(15)39), but most damage is very mild and reversible within 4 weeks (40). Since E-field gradient across neural membrane is influenced by numerous factors such as the thickness of the myelin sheet, unmyelinated C-fibers may be vulnerable to Efield exposure (14).…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%
“…At the cytokine levels, PRF could upregulate the expression of glia cell line-derived neurotrophic factor (33), decrease the presynaptic release of glutamate and citrulline (34), and induce spinal descending inhibitory pathways via 5-hydroxytryptamine 3 and α2 receptors (35). However, Choi et al (36) found that the expression of inflammatory proteins in the PRF and CRF groups was upregulated. The upregulated expression of inflammatory cytokines in the PRF group returned to normal after one month.…”
Section: Crf Pcrfmentioning
confidence: 99%